Contact lenses as a potential vehicle of Candida transmission - Michalcová, Lucie; Bednárová, Lucie; Šlang, Stanislav; Večeřa, Miroslav; Heidingsfeld, Olga (My University, 2024)
Purpose: Contact lenses can be contaminated with various microorganisms, including pathogenic yeasts of the genus Candida, which are known for their ability to adhere to abiotic surfaces, including plastic materials used for various medical purposes. Microbial contamination of the lenses can lead to infection of the wearer’s eyes. The purpose of this study was to simulate the contamination of contact lenses with C. albicans and C. parapsilosis, analyze the interaction of the microorganisms with the lens material, and optimize the protocol for PCR-based analysis of the microbial agents responsible for lens contamination. Methods: Hilafilcon lenses were exposed to C. albicans and C. parapsilosis cultures, washed, and examined for their ability to further spread the contamination. Scanning electron microscopy was used to analyze the attachment of yeast cells to the lenses. Infrared spectroscopy was used to examine the potential changes in the lens material due to Candida contamination. The protocol for DNA isolation from contaminated lenses was established to enable PCR analysis of microbes attached to the lenses. Results: Hilafilcon lenses contaminated with Candida were able to spread the contamination even after washing with saline or with a commercial cleaning solution. In the present experimental settings, the yeasts did not grow into the lenses but began to form biofilms on the surface. However, the ability of the lenses to retain water was altered. The PCR-based protocol could be used to help identify the type of contamination of contact lenses. Conclusion: Once contaminated with Candida albicans or Candida parapsilosis, Hilafilcon contact lenses are difficult to clean. Yeasts began to form biofilms on lens surfaces.
Kontaktní čočky jako potenciální nosič kvasinky rodu Candida
Keywords: Candida albicans; Candida parapsilosis; Contact lenses; Contamination; Candida albicans; Candida parapsilosis; kontaktní čočky; kontaminace